Exome sequencing of child–parent trios with bladder exstrophy: Findings in 26 children. Issue 10 (5th August 2021) - Pitsava, Georgia; Feldkamp, Marcia L.; Pankratz, Nathan; Lane, John; Kay, Denise M.; Conway, Kristin M.; Shaw, Gary M.; Reefhuis, Jennita; Jenkins, Mary M.; Almli, Lynn M.; Olshan, Andrew F.; Pangilinan, Faith; et al.
Abstract: Bladder exstrophy (BE) is a rare, lower ventral midline defect with the bladder and part of the urethra exposed. The etiology of BE is unknown but thought to be influenced by genetic variation with more recent studies suggesting a role for rare variants. As such, we conducted paired‐end exome sequencing in 26 child/mother/father trios. Three children had rare (allele frequency ≤ 0.0001 in several public databases) inherited variants in TSPAN4, one with a loss‐of‐function variant and two with missense variants. Two children had loss‐of‐function variants in TUBE1 . Four children had rare missense or nonsense variants (one per child) in WNT3, CRKL, MYH9, or LZTR1, genes previously associated with BE. We detected 17 de novo missense variants in 13 children and three de novo loss‐of‐function variants (AKR1C2, PRRX1, PPM1D) in three children (one per child). We also detected rare compound heterozygous loss‐of‐function variants in PLCH2 and CLEC4M and rare inherited missense or loss‐of‐function variants in additional genes applying autosomal recessive (three genes) and X‐linked recessive inheritance models (13 genes). Variants in two genes identified may implicate disruption in cell migration ( TUBE1 ) and adhesion ( TSPAN4 ) processes, mechanisms proposed for BE, and provide additional evidence for rare variants in the development of this defect.